Citizenship education: itineraries with children's literature - Ricardo, Cláudia (2021)
This study, which focuses on the issue of citizenship education, is based on an official document issued by the Portuguese Ministry of Education, entitled National Strategy for Citizenship Education (Estratégia Nacional de Educação para a Cidadania). The research question for this study was: “How can we educate for citizenship through children’s literature?”, and its goals were to get to know and understand children’s conceptions about racism, multiculturalism and migration, broadening their knowledge on these issues; and to reflect along with children based on practices aimed at promoting citizenship through children’s literature. The methodology was centred on an action-research approach, along the lines of reflection on the very teaching practice. The instruments used for collecting data were semi-structured interviews, participant observation and field notes, photographic and audio-visual records. The participants of the study were 3rd-grade students from an urban public primary education school. The results pointed to a greater knowledge and understanding of the phenomena under study by the children, after an intervention with children's literature. The vast majority of children were not only able to understand the concepts of racism, multiculturalism and migration, but also to take a critical stand on them.